(untitled) (IASH Indian Journal of Arid Horticulture, 2025)
The experiment was conducted to evaluate the bio-efficacy of a new anthranilic amide insecticide, Cyantraniliprole 10.26 OD, against aphids and thrips infesting pomegranate under the AICRP on Arid Zone Fruits at the Department of Horticulture, MPKV, Rahuri, during the Ambe bahar seasons from 2020-21 to 2022-23 on the Bhagwa variety of pomegranate. The four-year pooled data demonstrated that the application of Cyantraniliprole 10.26 OD at 0.75 to 0.9 ml per liter of water (75 90 g a.i./ha) was consistently effective in controlling aphids and thrips throughout the study period. The treatment resulted in significantly lower mean populations of aphids and thrips (2.1 to 6.18 and 1.74 to 3.65 per twig, respectively) compared to untreated control populations (24.9 and 14.47 per twig, respectively) on the 5th, 10th, and 15th days after two consecutive sprays. Cyantraniliprole 10.26 OD performed better than Lambda-cyhalothrin 5% EC, while Fipronil 5% EC and Spinosad 45 SC were the least effective treatments. Pooled yield and economic analysis revealed that Cyantraniliprole 10.26 OD at 0.9 ml per liter of water recorded the highest marketable fruit yield (15.26 t/ha) with a maximum cost-benefit ratio of 1:2.33 and an incremental cost-benefit ratio (ICBR) of 12.74. Based on these findings, it is recommended to apply two sprays of Cyantraniliprole 10.26 OD at 0.9 ml per liter of water at 15-day intervals during pest incidence for effective management of aphids and thrips on pomegranate.